Women’s status, empowerment, and utilization of skilled delivery services in Papua New Guinea: an empirical analysis based on structural equation modeling - Shen, Hao; Zhao, Hang; Wang, Baoqin; Jiang, Yi (Frontiers in Public Health, 2024)
Background Skilled birth attendants (SBA) facilitate identifying and overcoming labor problems and saving lives. With one of the highest maternal death rates in the Asia-Pacific area, SBA utilization during childbirth among Papua New Guinea (PNG) women remains low. Women’s status and empowerment are important factors in maternal and child health services and critical to maternal and child health development. This study is intended to apply structural equation modeling based on data from the Demographic and Health Survey (DHS) to evaluate the causal relationship between women’s status, empowerment, and SBA utilization in PNG and the mechanisms of their influence. Methods This study employed data from the 2016–2018 Papua New Guinea Demographic Health Survey (PNG DHS), which recruited 18,175 women aged 15–49 years. A multi-stage sample and a structured questionnaire were used to collect information on maternal health, women’s empowerment, and related topics. STATA 17.0 was used to describe the data, while MPLUS 8.2 was employed for structural equation modeling and pathway analysis. Results The two empowerment dimensions of household decision-making (standardized path coefficient, β = 0.049, p < 0.05) and access to health services (β = 0.069, p < 0.01) were positively associated with SBA utilization, while the association between attitudes toward partner violence and SBA utilization was not statistically significant. In addition, mediation analysis revealed that education indirectly influenced SBA utilization through access to health services (β = 0.011, 95% CI: 0.002, 0.022). Conclusion The findings confirmed the direct and indirect effects of women’s status and empowerment on SBA utilization in PNG. Therefore, a call for further evidence-based interventions in PNG and possibly Pacific Small Island Developing States (PSIDS) is needed to improve women’s educational attainment, household decision-making, and access to health services to enhance maternal and newborn health and well-being.